Accuracy of the tibiofemoral contact forces estimated by a subject-specific musculoskeletal model with fluoroscopy-based contact point trajectories - Dumas, Raphael; Moissenet, Florent (Journal of biomechanics, 2020)
Accurate estimation of the tibiofemoral contact forces relies on exact kinematics and joint geometry. Subject-specific kinematic constraints representing contact point trajectories derived from fluoroscopic measurements during lunge are introduced in a musculoskeletal model of the lower limb and compared to generic kinematic constraints. The medial, lateral, and total contact forces during gait and squat are validated using the data of four patients with an instrumented prosthesis. The accuracy of the estimated contact forces (both with subject-specific and generic kinematic constraints) remains close to the level reported in the literature. The mean root mean square errors range from 0.32 to 0.52 body weights for gait and from 0.27 to 0.72 body weights for squat. The impact of the subject-specific contact point trajectories is not found substantial or consistent between patients and tasks. Indeed, the kinematics of the total knee prostheses remains close to the kinematics of a hinge joint and the contact point locations remain generally centred at 20 mm from the tibia centreline (close to the constant value defined in the generic constraints). The contact point trajectories are also suspected to differ between tasks (lunge vs. gait and squat). While the contact point trajectories have been reported to be sensitive model parameters, no clear improvement of the contact force accuracy is demonstrated on patients with instrumented prosthesis. The introduction (as kinematic constraints) of fluoroscopy-based contact point trajectories may be considered in cases where these trajectories are significantly altered, as reported for osteoarthritis patients.